Pengembangan Sistem Informasi Persewaan Mobil memanfaatkan Payment Gateway (Studi Kasus : Rizky Transport Surabaya) - Amanda Rizky Rossitika; Widhy Hayuhardhika Nugraha Putra; Welly Purnomo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Rizky Transport Surabaya is a car rental service that was founded in 2007 and is still running today. The services provided to the community still use the conventional system, where the main component in the system is humans. The business process applied still uses a method where customers have to come to Rizky Transport to inquire about the availability of the car they want to rent, then make payments that must be face-to-face with a note which is also still written on the receipt book. The services provided make customers less comfortable so that customers cannot place orders quickly and are also less efficient in making payment transactions. Based on the problems that have been described, a solution can be found, namely making a car rental information system using the Midtrans Payment Gateway. This car rental information system will be integrated with a payment gateway using Midtrans as a payment gateway API service and developed using the waterfall model SDLC (System Development Life Cycle) method. The programming language used is PHP, Laravel framework, and MySQL database. The test carried out is validation testing using the blackbox testing method with a 100% valid success rate. Meanwhile, the usability test got 84% results, which means the system is categorized as very feasible. In the aspect of efficiency, the result is 4.25, which means the system has succeeded in providing satisfaction to users in placing orders and payments on the car rental information system.